DEVELOPMENT OF A COST-EFFECTIVE HEAVY-DUTY LEAD-ACID BATTERY_x000D_ CAPACITY TESTER - TERZİ, ÜMİT KEMALETTİN (My University, 2020)
Batteries are the energy source that provides energy to the vehicle for the first_x000D_ movement. Batteries used in motor vehicles nowadays are usually lead-acid_x000D_ batteries. This paper introduces the basic components of lead-acid batteries_x000D_ and describes the concept of a battery capacity test. The general definition of_x000D_ the standard for testing, EN50342, and the required conditions are presented._x000D_ Furthermore, a cost-effective capacity tester for heavy-duty lead-acid_x000D_ batteries in compliance with the standard was developed and introduced.